GOOD VILLAGE GOVERNANCE DI DESA AYUMOLINGO - Dikson Junus; Muten Nuna; Robby Hunawa; Nirmala A Sahi; Arifin Tumuhulawa (Governance, 2023)
The practice of good village governance has been pioneered and implemented since the outbreak of the reform era, during which the reformation of the government system led to a clean democratic process so that good governance is one of the reform tools that is absolutely necessary in the new government. However, if you look at the development of the implementation of good governance in Indonesia, especially in Ayumolingo Village, which has been running for about 15 years, it has not been fully successful in accordance with the aspirations of reform. This qualitative research by prioritizing primary data and secondary data, focuses on seeing how the application of the principle of transparency in governance towards good village governance in Ayumolingo Village and the factors that influence it? The conclusion is that the implementation of the principles of Good Village Governance in Ayumolingo Village, Gorontalo Regency, resulted in the application of the principle of transparency in Ayumolingo Village being good, but there is still a need for improvement from the aspect of community involvement in monitoring and supervising the governance of Ayumolingo Village. The factors that influence the application of the principle of transparency in the governance of Ayumolingo Village in realizing good village governance are coordination factors, physical factors and power factors.